EFEKTIVITAS KEMAMPUAN BERPIKIR KREATIF MATEMATIKA MELALUI MODEL THINK PAIR SHARE DI KELAS IV SD - Mutiara Triana Zain; F. Shoufika Hilyana; Diana Ermawati (Universitas Muhammadiyah Metro, 2024)
Students’ creative mathematical thinking abilities are low due to students’ lack of creativity and accuracy in developing ideas to solve problems. Apart from that, the use of learning models and media does not attract students’ interest. This research aims to analyze the increase in students’ creative thinking abilities in class IV SD 2 Gemiringlor before and after using the learning model Think Pair Share assisted by Tangram media. This research design uses a quantitative approach with methods Pre-Experimental by design One Group Pretest-Posttest. The data obtained through the written test method is a description test. The location of this research will be carried out in class IV of SD 2 Gemiringlor. The sample in this study was 20 class IV students using saturated sampling techniques. The results of this research show the percentage value N-Gain amounting to 56% which shows quite effective improvement. So, there is an increase in value pretest and posttest students before and after learning using the model Think pair Shrae with the help of Tangram media on the creative thinking abilities of fourth grade students at SD 2 Gemiringlor.